POLICING DESIRE: IDENTITY CONSTRUCTION IN MY POLICEMAN (2022) - Lea Zahra Santoso; Salva Syeira Wijaya; Yanti Rosalinah (Universitas Islam Sumatera Utara (UISU), 2026)
This study examines the tension between social duty and personal desire in My Policeman (2022), focusing on how individual identity is shaped and constrained by systemic social pressure. The analysis addresses three central issues: the mechanisms of identity suppression experienced by Tom Burgess, the influence of moral and societal norms on personal choice, and the broader ideological implications of these conflicts. Employing a qualitative descriptive approach, the study draws upon Feminist Literary Criticism, Queer Theory, and the Sociology of Literature to interpret the film’s narrative and character dynamics. The findings reveal that patriarchal expectations limit Marion’s autonomy, while heteronormative institutions compel Tom to repress his sexual identity, effectively criminalizing his private self. Rather than portraying social expectations merely as cultural pressures, the film presents the legal and moral framework of 1950s Britain as an active “policing force” that regulates private emotions and desires. This perspective offers a deeper understanding of how desire becomes socially monitored and ideologically controlled. Ultimately, the study demonstrates that these restrictive structures not only suppress personal freedom but also fracture emotional integrity and undermine authentic human relationships.